Oral cryotherapy for management of chemotherapy‐induced oral mucositis in haematopoietic cell transplantation: a systematic review - Faizah Jabr Alsulami (BMC Cancer, 2022)
Abstract Background Oral mucositis (OM) is known to be the most common and challenging side effect of conditioning chemotherapy in haematopoietic cell transplant (HCT). This side effect causes significant morbidity and may delay the treatment plan, as well as increase therapeutic expenses. There are few clinical trials in the literature that indicate any kind of treatment or prevention methods are effective. Therefore, the aim of this study is to perform a systematic review of literature and examine the effectiveness of oral cryotherapy (OC) in management of chemotherapy-induced OM in patients with haematological malignancies undergoing a HCT. Methods A systematic literature search was conducted, using the electronic databases PubMed, Embase, MEDLINE and Scopus. A total of 322 papers were identified and 9 papers were analysed based on defined inclusion and exclusion criteria. The quality of the chosen primary studies was appraised using the COCHRANE risk of bias assessment tool. Results Nine randomized controlled trials, analysing 658 participants; control group (n = 289, age mean ± SD; 41.15 ± 21) and treatment group (n = 369, age mean ± SD; 39.15 ± 20), were included in this systematic review. Seven studies had significantly addressed the effectiveness of OC (p value < 0.05), in reducing the incidence of developing severe OM in the adult population undergoing HCT, especially when the conditioning regimen protocols included high dose of alkylating agent such as melphalan. Conclusion This review supports the use of OC for prevention of OM in patients undergoing HCT, with high-dose of melphalan conditioning protocols. It is recommended that more studies be conducted to compare efficacy and duration of OC with other chemotherapeutic agents with relatively short plasma half-lives. The heterogeneity of the trials demonstrated the need to regulate the validated assessment tools and similar interventions that would enable comparisons and analyses of treatment effects based on well-designed RCTs.